Primary dysmenorrhea, premenstrual tension and symptoms preceding menstruation in a group of physiotherapy students (International Seven Journal of Health Research, 2023)
Introduction: Primary dysmenorrhea is pain in the lower abdomen, which appears in the first few days before menstruation and during the follicular phase. As a result, premenstrual symptoms accompany women during several different cycles of the month, as well as during menstruation. The study of premenstrual symptoms is developing and evolving every day in order to inform and help the female population. Objective: This study aimed to analyze possible cases of Primary Dysmenorrhea, PMS (Premenstrual Tension) and Symptoms that Precede Menstruation in a Group of Physiotherapy Students. Methodology: This is a descriptive, exploratory and quantitative research, where possible cases of Primary Dysmenorrhea, PMS (Premenstrual Tension) and Symptoms that Precede Menstruation were analyzed in a group of 37 students of the Physiotherapy Course. Results: It was observed that 38% of the female students reported anxiety during their period, 35% reported feeling the urge to cry, 43% food cravings, 41% headaches, 41% bloating, 43% felt changes in their relationships with work colleagues, 49% in their social life activities, 27% reported making moderate use of medication, while 24% made continuous use of contraceptive methods. Conclusion: It was therefore possible to observe from the survey that many students have symptoms resulting from premenstrual tension, as well as their interference in daily life and the means used to treat the symptoms.